Pengaruh Pengunaan Media Audiovisual oleh Guru PAK terhadap Minat Belajar Siswa Kelas VIII SMP Negeri 1 Sianjur Mula-Mula Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Selvia Novalina Marpaung; Frainskoy Rio Naibaho; Hisardo Sitorus; Raikhapoor Raikhapoor; Lince R.T Simamora (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
The research aims to determine the effect of the use of audiovisual media by PAK teachers on the learning interest of class VIII students at SMP Negeri 1 Sianjur Mula at Samosir Regency for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the use of audiovisual media by PAK teachers on the learning interest of class VIII students at SMP Negeri 1 Sianjur Mula at Samosir Regency for the 2023/2024 academic year. Descriptive and inferential quantitative research methods. The population of all class VIII students at SMP Negeri 1 Sianjur Initially in Samosir Regency for the 2023/2024 academic year who are Protestant Christians is 123 people. The sample was random (random sampling), namely 50% of the total population, namely 62 people. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value of rcount=0.576> rtable=0.254 and tcount=5.458> ttable=2.00030 shows that there is a positive and significant relationship between the use of audiovisual media by PAK teachers and the learning interest of class VIII students at SMP Negeri 1 Sianjur Mula -starting with Samosir Regency for the 2023/2024 Academic Year. b) Regression equation. c) The determination test revealed that the magnitude of the effect was 33.18%. d) Hypothesis testing obtained Fcount=28.971>Ftable=3.15 then H0 (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. The research concluded that there was a positive and significant influence between the use of audiovisual media by PAK teachers on the learning interest of class VIII students at SMP Negeri 1 Sianjur Mula at Samosir Regency for the 2023/2024 academic year.